Home Sanitation and Clean Water Facilities in Stunting Cases at the Lampihong Health Center Area, Balangan - Heriyani, Farida; Farida, Ainun; Ulfah, Maria (Fakultas Kedokteran Universitas Lambung Mangkurat, 2023)
Stunting is a condition of growth failure in children under five years old (toddlers) due to chronic malnutrition and recurrent infections, especially in the first 1,000 days of life. One of the indirect causes is the availability of clean water and poor sanitation. Lampihong Community Health Center Balangan Regency is one of the areas with the highest stunting cases in South Kalimantan. This study aims to analyze the relationship between home sanitation and clean water facilities with the incidence of stunting in the Lampihong Community Health Center, Balangan Regency. The research method is analytic observational with a case control approach. The research sample consisted of 30 mothers of stunted toddlers as the case group and 30 mothers of non-stunted toddlers as the control group. Data analysis used the chi square test at a 95% confidence level. The research results showed that the majority of stunted toddlers lived in houses with unhealthy water closet, wastewater disposal and waste management that did not meet the requirements. Most of the stunted and non-stunted toddlers use clean water that meets the requirements. The results show that there is a significant relationship between home sanitation that does not meet the requirements and the incidence of stunting in toddlers, but there is no significant relationship between clean water facilities and the incidence of stunting in toddlers in the Lampihong Health Center, Balangan Regency.